The ERG1 K+ Channel and Its Role in Neuronal Health and Disease - Sanchez-Conde, Francisco G.; Jimenez-Vazquez, Eric N.; Auerbach, David S.; Jones, David K. (Frontiers in Molecular Neuroscience, 2022)
The ERG1 potassium channel, encoded by KCNH2, has long been associated with cardiac electrical excitability. Yet, a growing body of work suggests that ERG1 mediates physiology throughout the human body, including the brain. ERG1 is a regulator of neuronal excitability, ERG1 variants are associated with neuronal diseases (e.g., epilepsy & schizophrenia), and ERG1 serves as a potential therapeutic target for neuronal pathophysiology. This review summarizes the current state-of-the-field regarding the ERG1 channel structure and function, ERG1’s relationship to the mammalian brain and highlights key questions that have yet to be answered.